Effect of salt-tolerant plant growth-promoting rhizobacteria inoculation on crop growth, biochemical properties and yield of rice - Shultana, Rakiba (2020)
Soil salinity causes huge negative impacts on the global agricultural sector and is currently a crucial issue in wetland rice production (Oryza sativa L). Due to the unsatisfactory results of conventional salinity mitigation practices, the use of indigenous salt-tolerant plant growth-promoting rhizobacteria (PGPR) on existing rice cultivar could be a new alternative. A series of experiments were conducted under laboratory and glasshouse conditions to fulfill the following objectives; i) to screen for potential salt-tolerant PGPR from coastal salt-affected rice cultivation areas; ii) to select suitable rice varieties for an optimum response towards inoculation of salt-tolerant PGPR; iii) to elucidate the mechanism of salt-tolerant PGPR inoculation on improving crop growth, biochemical properties, and yield of rice. In experiment 1, a total of 44 strains were isolated and screened based on their qualitative salinity tolerance and plant growth-promoting properties. These isolates were subjected to quantitative screening at five levels of NaCl concentrations (0, 0.5, 1, 1.5, and 2M) and the results showed that three isolates labeled as UPMRB9, UPMRE6, and UPMRG1 were able to grow on the highest NaCl-amended media and maintained a relatively high bacterial population. Isolate UPMRB9 produced the highest amount of exopolysaccharides (31.5 g L-1) and absorb the highest amount of sodium (24.8 mg L-1) on 1.5M of NaCl-amended media. UPMRE6 and UPMRB9 produced the highest floc yield (22.97 g L-1) and biofilm (OD 1.37), respectively, both on 1M of NaCl-amended media. The characteristics of UPMRB9 as a salt-tolerant isolate were supported by the Scanning Electron Microscope (SEM) observation which showed higher EPS, floc yield, and biofilm formation when exposed to salt stress condition. The beneficial characterization studies also revealed UPMRB9 as the highest Indole Acetic Acid (IAA) producer. Besides, UPMRE6 recorded the highest phosphate and potassium solubilizations in all NaCl-amended media. These three potential isolates namely UPMRB9, UPMRE6, and UPMRG1 were identified using 16s rRNA gene sequence technique, and the blast results revealed 99% similarity with Bacillus tequilensis, Bacillus aryabhattai, and Providencia stuartii, respectively. The characterization of EPS extracted from the bacterial isolates showed the presence of hydroxyl, carboxyl, amino, sulfhydryl, and phosphate functional groups which have shown a strong binding affinity to toxic Na+. In experiment 2, a glasshouse study was conducted involving seven rice varieties that were exposed to four different levels of salinity (0, 4, 8, 12 dSm-1) at the seedling stage. Based on the morpho-physiological and biochemical respond towards salt stress, three rice varieties namely BRRI dhan67, Putra-1, and MR297 were identified as salt-tolerant, moderately salt-tolerant, and salt-susceptible varieties, respectively, and were selected for further study. In experiment 3, the selected isolates (UPMRB9, UPMRE6, and UPMRG1) were inoculated to the salt-responsive rice varieties (BRRI dhan67, Putra-1, and MR297) at the seedling stage under 8 dSm-1 of salinity. Results showed that inoculation of UPMRB9 to BRRI dhan67 produced significantly highest seedling dry matter (1.50 g) due to the increased chlorophyll and relative water content, and reduced electrolyte leakage and the ratio of Na/K in the inoculated plants. In experiment 4, the plant inoculation test was extended up to yield stage involving 2 strains of UPMRB9 and UPMRE6. Results showed that inoculation of UPMRB9 to the rice variety Putra-1 responded for the highest rate of photosynthesis (10.52 μmol CO2 s-2m-1), proline content (10.48 μmol g-1 FW), total soluble sugar content (6.29 mg g-1 FW), superoxide dismutase (SOD) production (89.70 unit mg-1 FW) and uptake of phosphorous (4.64 g/plant). The higher accumulation of osmoprotectants like proline and total soluble sugar in Putra-1 rice markedly improved the regulation of antioxidant enzymes and thus improved plant resistance to salinity which eventually enhanced plant photosynthesis. Besides, BRRI dhan67 treated with UPMRB9 highly responded towards augmenting stomatal conductance, malondialdehyde (MDA) content, catalase (CAT) production, higher uptake of K and Ca, along with increasing the yield parameters of 1000 grain weight (27.33g), filled grains (79%) and grains per plant (27.66g). In this case, UPMRB9 assisted uptaking higher amounts of K and Ca, which helped towards achieving maximum grains of BRRI dhan67 through reducing the toxicity of Na+. Considering all these positive traits, it can be concluded that the locally-isolated salt-tolerant bacterial strains could contribute significantly towards improving the physiological and biochemical characters and grain yield components of rice plants under salt stress conditions. These promising PGPR strains can be a potential biofertilizer inoculant to mitigate the problems raised due to the global climate change for coastal rice cultivation. This study has successfully demonstrated the possible salt-tolerance mechanism of PGPR and response of their inoculation on different local rice varieties under salt stress conditions especially under the Malaysian rice cultivation scenario which has not been studied in detail previously.